Pelatihan Bahasa Inggris Business Letter Writing untuk Meningkatkan Daya Saing Pelaku UMKM dalam Pemasaran Produk Di Bisnis Global - Sari, Valentina Dyah Arum (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2020)
Community service to support the needs of entrepreneurs for Small and Medium in Yogyakarta was begun with conducting workshop for members of IPEMI Yogyakarta and PERWIRA Yogyakarta. IPEMI is the Association of Indonesian Muslim Entrepreneurs while PERWIRA is the Indonesian Women's Entrepreneur Association, both of them are committed to supporting entrepreneurs of Small and Medium Enterprises, especially those in Yogyakarta. By conducting business letter training for Small and Medium actors, members of IPEMI Yogyakarta and PERWIRA Yogyakarta, it can be an effective step to prepare Small and Medium Yogyakarta in MEA. In this training discussed some things about the business letter, including an introduction to what is meant by a business letter, parts of the business letter as well as examples of business letters that are close and will even be used by Small and Medium Enreprises’ doers in the trade sector. The delivery of material applied lecturing methods and interactive dialogue. In this workshop, the participants were also asked to practice compiling one business letter by paying attention to the instructor's explanation and examples written in the module. The business letter writing training went well and successfully to the Small and Medium Enterprises’ doers who are currently required to use e-commerce which is mostly communication is done in written English. Further, the enterpreneurs of Small and Medium Enterprises now currently gain the knowledge and ability to use and response business letters appropriately.